2021
DOI: 10.3390/cells10123274
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-214 in Health and Disease

Abstract: MicroRNAs (miRNAs) are endogenously expressed, non-coding RNA molecules that mediate the post-transcriptional repression and degradation of mRNAs by targeting their 3′ untranslated region (3′-UTR). Thousands of miRNAs have been identified since their first discovery in 1993, and miR-214 was first reported to promote apoptosis in HeLa cells. Presently, miR-214 is implicated in an extensive range of conditions such as cardiovascular diseases, cancers, bone formation and cell differentiation. MiR-214 has shown pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 176 publications
0
13
0
Order By: Relevance
“…It was reported that miR-214 in HUVEC cells is low in the absence of lesions. 45 However, miR-214 shows a higher expression level in breast cancer cells than in normal tissue. 42 Then images were collected using a confocal fluorescence microscope.…”
Section: Intracellular Imaging Of Tdfm Nanoprobesmentioning
confidence: 99%
“…It was reported that miR-214 in HUVEC cells is low in the absence of lesions. 45 However, miR-214 shows a higher expression level in breast cancer cells than in normal tissue. 42 Then images were collected using a confocal fluorescence microscope.…”
Section: Intracellular Imaging Of Tdfm Nanoprobesmentioning
confidence: 99%
“…First mir-214 was reported to promote apoptosis in HeLa cells. Presently, mi-214 is implicated in an extensive range of conditions such as cardiovascular diseases, cancers, bone formation and cell differentiation [28]. For mir-214-5p and the seed sequence GCCUGU, one finds the surface f (A2) 1,{1:0:0:0} (x, y, z) = xyz + y 2 + z 2 − 4 within G mir−214−5p (0, 0, 0, 0), as shown in Figure 5.…”
Section: Sl(2 C) Scheme Processing In Micrornasmentioning
confidence: 99%
“…No adverse effects of rAAV9 carrying miR-214-3p TuD or miR-34a-5p in mice Previous studies have demonstrated that miR-214-3p plays roles in various biological processes, including skeletal development and homeostasis, cancer development, immune responses, skeletal muscle development, ischemic injury in the heart, and angiogenesis, 41 while miR-34a-5p is important for the regulation of multiple target genes involved in cancer cell growth, proliferation, apoptosis, and invasion. [42][43][44] Given their expression and pleiotropic roles in various tissues, we tested whether rAAV9-mediated inhibition of miR-214-3p or overexpression of miR-34a-5p causes any untoward adverse effects on non-skeletal tissues.…”
Section: Raav9-mediated Expression Of Mir-214-3p Tud or Mir-34a-5p Re...mentioning
confidence: 99%